Active surveillance for asymptomatic kidney stones - Önal, Bülent; Özman, Oktay (Cerrahpaşa Medical Journal, 2019)
Despite the advances in the management of urinary tract stone disease, data on the natural history of stones are insufficient. Therefore, the aim of this review is to present the natural history of asymptomatic kidney stones and the results of their active surveillance in the light of the current studies.Taking into account the current findings, it can be said that asymptomatic kidney stones transit spontaneously in 3%–30% of patients, become symptomatic in 12%–50%, and necessitate active treatment in 10%–26%. Active surveillance may be recommended in appropriate cases considering the results of prophylactic treatments. Cite this article as: Özman O, Önal B. Active Surveillance for Asymptomatic Kidney Stones. Cerrahpasa Med J 2019; 43(1): 1-5.